Association of Retroplacental Blood With Basal Plate Myofibers. (July 2018) - Wyand, Rachel; Cramer, Stewart F; Oshri, Assaf; Heller, Debra S
Objectives: Diagnosed clinical abruption showing blood clot should be signed out in the pathology report as retroplacental hemorrhage with or without parenchymal indentation, and submitted clot separate from the placenta should be weighed. In our experience, some cases sent as clinical abruptions have been cases of morbid adherence. This study was undertaken to evaluate the association of retroplacental blood with basal plate myofibers (BPMF). Methods: One hundred fifty-six placentas reviewed by a board-certified pediatric pathologist at a community hospital were evaluated for significant retroplacental blood. Basal plates were reviewed for deviations from normal. Results: Of the 156 placentas, 33 (21%) had significant retroplacental blood; 21/156 (13%) had a separate clot, of which 11/21 (52%) had BPMF. Eleven BPMF-associated separate clots ranged from 10.5 to 60 g (average 23), while the clots of 10 cases with no demonstrated BPMF ranged from 19 to 440 g (average 82), tending to be larger ( p  < .03). Basal plate damage prior to delivery was noted in both sets of placentas. BPMF placentas could have myometrial damage prior to delivery. Conclusions: Since BPMF may confer a risk for accreta in a subsequent pregnancy, submission of a separate clot with the placenta should lead the pathologist to evaluate for basal plate myofibers on H&E and consider if there is an evidence-based indication to do an actin stain, before presuming a diagnosis of abruption.